Heterojunction-based silver-coated copper paste and application thereof

By using a combination of silver-clad copper powder with low silver content and high silver content in silver-clad copper powder, combined with the use of thermosetting resin and thermoplastic resin, and adding microcrystalline ultrafine silver powder, the silver-clad copper powder in the prior art has been solved. It is difficult to reduce the overall silver content, achieving high electrical performance and low cost effects.

CN119480212APending Publication Date: 2025-02-18ZHEJIANG ZHONGXI ELECTRONICS TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411670748.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, while maintaining good electrical properties, it is difficult to further reduce the overall silver content, which cannot meet the market's demand for less silver.

Method used

The components of the silver-clad copper paste are adjusted by using a combination of low-silver content and high-silver content in the silver-clad copper paste, combined with the use of thermosetting resin and thermoplastic resin, and the addition of microcrystalline ultrafine silver powder, the components of the silver-clad copper paste are adjusted by using a combination of low-silver content and high-silver content in the silver-clad copper paste, combined with the use of thermosetting resin and thermoplastic resin, and the addition of microcrystalline ultrafine silver powder, the components of the silver-clad copper paste are adjusted by using a combination of low-silver content and high-silver content in the silver-clad copper paste, combined with the use of thermosetting resin and thermoplastic resin, and the addition of microcrystalline ultrafine silver powder. proportions to optimize electrical performance.

Benefits of technology

It realizes that while reducing the total silver content, the electrical properties of the silver-clad copper paste are maintained or improved. The volume resistivity is less than 8.0μΩ·cm, and the adhesion is excellent. It is suitable for promotion in production practice.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480212A_ABST
    Figure CN119480212A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of solar photovoltaic cell paste, and particularly relates to heterojunction-based silver-coated copper paste and application thereof. The silver-coated copper paste comprises the following components: silver-coated copper powder, submicron silver powder, a binder, a curing agent and a solvent. The silver-coated copper powder is a combination of low-silver silver-coated copper powder and high-silver silver-coated copper powder; the silver content of the low-silver silver-containing coated copper powder is less than 15%, and the silver content of the high-silver silver-containing coated copper powder is greater than 15%; the low-silver silver-containing coated copper powder accounts for 5-70% of the total mass, and the high-silver silver-containing coated copper powder accounts for 1-50% of the total mass; the curing agent is a combination of thermosetting resin and thermoplastic resin. By selecting the components and the content, the conductivity of common paste with the silver content of 50% or above in the market can be achieved with the silver content of about 35%, the cost is remarkably reduced, the adhesive force is excellent, and the conductive paste is suitable for being popularized in production practice.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solar photovoltaic cell slurry, and in particular relates to a silver-coated copper slurry based on a heterojunction and an application thereof. Background Art

[0002] N-type heterojunction photovoltaic (Heterojunction with Intrinsic Thin Layer, referred to as HIT or HJT) cells are high-performance cells made on N-type monocrystalline silicon substrates. HJT photovoltaic technology has the advantages of high photoelectric conversion efficiency, low attenuation, and high bifaciality. The theoretical photoelectric conversion efficiency of HJT cells can reach 28.7%, and the current mass production efficiency has exceeded 26.0%, with good market prospects. The formation temperature of the amorphous silicon thin film in HJT cells is about 200°C. In order to prevent this layer from being damaged by the high temperature of the subsequent metallization process, HJT cells use low-temperature silver paste. Unlike high-temperature silver paste, which mainly uses lead-containing glass powder, low-temperature silver paste forms a conductive path through the curing and cross-linking of polymer resins.

[0003] Silver reduction and de-silverization are important directions for the research and development of photovoltaic technology. Silver-coated copper technology is currently an effective way to reduce the cost of HJT low-temperature silver paste. For example, patent 202311302687.X discloses a low-silver heterojunction silver-coated copper paste and its preparation method. The silver-coated copper paste in the invention includes: 10-50% micron-grade silver powder, 0-50% nano-grade silver powder, 40-80% silver-coated copper powder, 2-10% epoxy resin, 0.5-3% curing agent, 0.1-0.5% welding aid, 0.1-5% epoxy diluent and the rest of the solvent. The silver content of the silver-coated copper powder in this technical solution is 20%, and the final overall silver content of the electrode is about 55%, which can reach a resistivity ranging from 5.1 to 11.6 μΩ·cm. It can be seen that due to the high silver content of the silver-coated copper powder and other factors, the overall silver content of the technical solution is high and the electrode performance is poor, which makes it difficult to meet the current market requirements for less silver.

[0004] In heterojunction silver-coated copper slurry, it is usually necessary to add a binder to make a variety of particles form a uniform slurry. Common binders are thermosetting resins such as epoxy resins. Although they do not directly participate in the formation of heterojunctions, different binders still affect the final performance of the silver-coated copper slurry. For example, patent 202110397851.4 discloses a silver paste for heterojunction batteries and its preparation method and application, wherein the binder A includes at least one of a polyester resin and an epoxy resin, and the binder B is a phenolic resin modified with white carbon black. This technical solution enhances the adhesion of the cured silver paste to the battery substrate through special adhesive selection, reduces contact resistance, and improves electrical performance. The silver-coated copper paste in this technical solution can achieve a higher photoelectric conversion efficiency with a total silver content of more than 60%, and the resistivity ranges from 4 to 8 μΩ·cm.

[0005] Compared with precious metal silver, copper price is only about 1% of silver price, which has a great cost advantage. Compared with traditional crystalline silicon cells, the production cost of HJT cells per watt is 0.07 yuan higher, of which the silver paste accounts for nearly 50% of the cost increase. Therefore, the silver content in silver-coated copper paste is an important indicator for evaluating the marketability of silver-coated copper paste. Therefore, how to improve the electrical properties of silver-coated copper paste while minimizing the dependence on the high conductivity of silver is an urgent problem to be solved. Summary of the invention

[0006] The present invention aims to overcome the defect in the prior art that it is difficult to further reduce the overall silver content of the silver-coated copper paste while having good electrical properties, and provides a silver-coated copper paste based on a heterojunction and its application to overcome the above defect.

[0007] In order to achieve the purpose of the above invention, the present invention is implemented by the following technical solutions: A silver-coated copper paste based on a heterojunction comprises the following components: Silver-coated copper powder, submicron silver powder, binder, curing agent and solvent; The invention is characterized in that: the silver-coated copper powder is a combination of low-silver-containing silver-coated copper powder and high-silver-containing silver-coated copper powder; The silver content of the low-silver silver-coated copper powder is less than 15%, and the silver content of the high-silver silver-coated copper powder is greater than 15%; The low-silver silver-containing copper powder accounts for 5-70% of the total mass, and the high-silver silver-containing copper powder accounts for 1-50% of the total mass; The curing agent is a combination of a thermosetting resin and a thermoplastic resin.

[0008] Gradually replacing silver with copper as electrode slurry is an important way to reduce the cost of HJT batteries. However, copper is easily oxidized in the air, resulting in a sharp increase in resistance. Silver-coated copper powder is based on copper powder, and a layer of silver is plated on the surface of the copper powder by wet chemical plating to form a core-shell structure with copper as the core and silver as the shell. By regulating the thickness of the silver layer, the silver content and copper content of the silver-coated copper powder can be regulated. The silver content of the silver-coated copper powder used in the silver-coated copper paste based on HJT photovoltaics is usually between 10wt% and 30wt%. The copper core and silver shell structure used in the silver-coated copper powder allows the copper to be protected by the silver layer and not oxidized during heat treatment, thereby maintaining the electrical properties of the silver-coated copper paste well. In the present invention, silver-coated copper powder with a silver content of less than 15% is referred to as low-silver silver-coated copper powder, and silver-coated copper powder with a silver content of more than 15% is referred to as high-silver silver-coated copper powder. In practice, the silver content of low-silver-containing silver-clad copper powder is between 5-15%, and the silver content of high-silver-containing silver-clad copper powder is between 15-50%.

[0009] The way to control the overall silver content of silver-coated copper paste in the prior art is mainly to change the ratio of pure silver powder to silver-coated copper powder. In practice, if the silver content in the silver-coated copper powder is reduced, more pure silver powder must be added to ensure the overall electrical performance, which has limited cost reduction, and blindly reducing the silver content in the silver-coated copper powder may cause the coverage rate to decrease and affect the antioxidant performance. The present invention has found through multiple experiments that by adjusting the ratio of low-silver-containing silver-coated copper powder to high-silver-containing silver-coated copper powder, it is easier to achieve good electrical properties. Since the silver-coated copper paste needs to undergo a high-temperature sintering process in actual use, it may be that the powder with a high silver content increases the sintering activity during the sintering process, so that the powder with a low silver content can also sinter better, thereby improving the overall sintering performance and further improving the overall electrical properties.

[0010] Generally speaking, the silver-coated copper paste is used to prepare electrodes. The silver-coated copper paste is first screen-printed onto the silicon wafer of the solar cell, and then the solvent part is removed by pre-drying, and finally sintered at high temperature to form a good electrical contact between the silver-coated copper powder and the silicon wafer, and the organic carrier is removed at the same time to form a dense electrode. During the whole process, it is necessary to undergo multiple drastic temperature changes. Since the thickness of the silver layer coated on the copper is different, the thermal expansion coefficients of the low-silver-containing silver-coated copper powder and the high-silver-containing silver-coated copper powder are different, resulting in thermal stress when the temperature changes, which affects the formation of the conductive path in the electrode. Therefore, the present invention simultaneously adds a thermosetting resin and an appropriate amount of thermoplastic resin. On the one hand, the thermosetting resin forms the basic skeleton of the electrode, and the thermoplastic resin improves the toughness of the electrode to prevent the electrode from cracking during expansion and contraction; on the other hand, the thermoplastic resin can well adjust the stress distribution during the sintering process, reduce the influence of thermal stress on the electrode structure, and the thermoplastic resin can fill the microscopic gap, further optimize the microstructure, and improve the density and uniformity of the electrode. But at the same time, the amount of thermoplastic resin added should not be too large, otherwise it will affect the overall structural strength and conductivity of the electrode. After many experiments, it was found that the addition ratio of thermosetting resin to thermoplastic resin is preferably 1:0.01-0.15.

[0011] Preferably, the silver-coated copper paste further comprises microcrystalline ultrafine silver powder, which accounts for 1-30% of the total mass. The microcrystalline ultrafine silver powder referred to in the present invention refers to a plurality of microcrystals formed by the mutual agglomeration of 3-50 silver particles. The microcrystalline ultrafine silver powder has a morphology as shown in the attached Figure 3 As shown. After many experiments, it was found that in the system of low-silver silver-coated copper powder and high-silver silver-coated copper powder, adding the above-mentioned microcrystalline ultrafine silver powder can effectively improve the conductivity of the silver-coated copper paste. This may be due to the special structure of the microcrystalline, which increases the probability of mutual contact between silver-containing particles of different components and different particle sizes, thereby facilitating the formation of a conductive path. The particle size D50 of the microcrystalline ultrafine silver powder described in the present invention is between 0.8-1.6μm, preferably 1.0-1.4μm, and the tap density is 4.0-6.0 g / cm 3 ; Specific surface area is 0.8-1.5 m 2 / g.

[0012] Preferably, the thermosetting resin is an epoxy resin, and the thermoplastic resin is a phenoxy resin. The weight average molecular weight Mw of the phenoxy resin is between 10,000 and 100,000.

[0013] Preferably, the epoxy resin is a combination of one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, glycidyl ester epoxy resin and the like.

[0014] Preferably, the low-silver silver-containing copper-coated powder is a mixed powder of spherical and flake shapes, with a particle size D 50 Preferably, the silver content is about 10%, and the particle size D 50 The diameter is 2.5-3.5μm, and the tap density is 4.0-6.0 g / cm 3 , with a specific surface area of ​​0.2-0.6 m 2 / g.

[0015] Preferably, the high-silver silver-containing copper-coated powder is a spherical powder with a particle size D 50 Preferably, the silver content is about 20%, and the particle size D 50 The diameter is 3.2-4.5μm, and the tap density is 4.0-6.0 g / cm 3 , with a specific surface area of ​​0.2-0.6 m 2 / g.

[0016] Preferably, the curing agent includes one or more of a latent epoxy curing agent and an isocyanate latent curing agent. Preferably, the latent epoxy curing agent is one or more of a fatty amine curing agent, an acid anhydride curing agent, a dicyandiamide curing agent, an imidazole curing agent, a microcapsule curing agent, and the like.

[0017] Preferably, the isocyanate latent curing agent is a combination of one or more of toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, hexylene diisocyanate, xylylene diisocyanate and isophorone diisocyanate.

[0018] Preferably, the solvent is a combination of one or more of diethylene glycol ethyl ether acetate, butyl carbitol acetate, dibasic acid ester, terpineol, ethylene glycol butyl ether acetate, butyl carbitol, and the like.

[0019] On the other hand, the present invention also discloses the application of the above silver-coated copper paste based on heterojunction in the preparation of gate line electrodes.

[0020] Therefore, the present invention has the following beneficial effects: (1) The present invention can achieve better electrical properties while reducing the total silver content of the slurry by compounding silver-coated copper powders with different silver contents. The conductivity of the slurry with a silver content of about 35% can reach the same level as the slurry with a silver content of more than 50% commonly found on the market.

[0021] (2) The present invention improves the mechanical properties and electrical conductivity of the prepared electrode by the combination of the binder, and further improves the formation of the conductive path in the electrode by adding microcrystalline ultrafine silver powder, thereby effectively reducing the resistivity of the prepared electrode. (3) The cost of the silver-coated copper paste of the present invention is significantly lower than that of the paste with a silver content of more than 50% commonly found on the market. Experimental verification shows that the volume resistivity is lower than 8.0 μΩ·cm and the adhesion is excellent, which is suitable for promotion in production practice. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope image of low-silver-containing silver-coated copper powder and a distribution map of copper and silver elements.

[0023] Figure 2 This is a scanning electron microscope image of high-silver-containing silver-coated copper powder and a distribution map of copper and silver elements.

[0024] Figure 3 This is a scanning electron microscope image of microcrystalline ultrafine silver powder.

[0025] Figure 4 Printing patterns for paste resistivity testing. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0027] As shown in Table 1 below, the silver content, morphology, particle size distribution (D10, D50, D90), tap density and specific surface area of ​​each powder used in the embodiments of the present invention are listed.

[0028] Among them, #1 silver-coated copper powder is low-silver-containing silver-coated copper powder with a silver content of about 10%, and its morphology is a mixture of spherical powder and flaky powder; #2 silver-coated copper powder is high-silver-containing silver-coated copper powder with a silver content of about 20%, and its morphology is spherical powder. Figure 1 This is the SEM distribution diagram of silver and copper elements in #1 silver-coated copper powder. As shown in the figure, the silver element is evenly coated on the surface of the copper powder. Figure 2 This is the SEM distribution diagram of silver and copper elements in #2 silver-coated copper powder. As shown in the figure, the silver element is evenly coated on the surface of the copper powder. Figure 3 This is an electron microscope image of microcrystalline ultrafine silver powder.

[0029] The preparation process of the silver-coated copper paste of the present invention is as follows; S1. Mix 250 g of phenoxy resin and 750 g of diethylene glycol ethyl ether acetate (DCAC) solvent and add them to the reactor. Set the stirring paddle at 200 rpm and the temperature at 80°C. Stir and dissolve for about 4 to 6 hours until the resin is completely dissolved. After the resin is completely dissolved, cool the resin solution to room temperature, add 25 g of isocyanate latent curing agent, and continue stirring at 200 rpm for 1 hour to obtain a phenoxy carrier. The phenoxy resin content in the phenoxy carrier is about 24%; S2, adding epoxy resin, latent epoxy curing agent, phenoxy carrier and solvent and other organic components in accordance with the ratio of mass to a suitable container in sequence, and selecting a suitable mixer or homogenizer according to the volume of the mixture to stir the mixture evenly, thereby obtaining a silver-coated copper slurry carrier; S3. Add low-silver-containing silver-coated copper powder, high-silver-containing silver-coated copper powder, submicron silver powder and microcrystalline ultrafine silver powder to the silver-coated copper paste carrier in accordance with the ratio of mass, stir evenly with a mixer or homogenizer, and roll with a three-roll mill to reduce the fineness to less than 5 microns to obtain a silver-coated copper paste.

[0030] Example 1 A silver-clad copper paste based on heterojunction, calculated by mass grouping, includes: #1 silver-coated copper powder 10.37%, #2 silver-coated copper powder 41.76%, submicron silver powder 25.54%, microcrystalline ultrafine silver powder 14.32%, epoxy resin 2.75%, epoxy curing agent 0.23%, phenoxy carrier 0.12%, DCAC solvent 4.91%.

[0031] According to the above preparation process, a uniformly dispersed silver-coated copper slurry is obtained.

[0032] Example 2 A silver-clad copper paste based on heterojunction, calculated by mass grouping, includes: #1 silver-coated copper powder 35.54%, #2 silver-coated copper powder 21.38%, submicron silver powder 27.99%, microcrystalline ultrafine silver powder 6.76%, epoxy resin 2.03%, epoxy curing agent 0.1%, phenoxy carrier 0.76%, DCAC solvent 5.44%.

[0033] According to the above preparation process, a uniformly dispersed silver-coated copper slurry is obtained.

[0034] Example 3 A silver-clad copper paste based on heterojunction, calculated by mass grouping, includes: #1 silver-coated copper powder 49.01%, #2 silver-coated copper powder 10.81%, submicron silver powder 27.02%, microcrystalline ultrafine silver powder 5.94%, epoxy resin 1.33%, epoxy curing agent 0.1%, phenoxy carrier 0.75%, DCAC solvent 5.04%.

[0035] According to the above preparation process, a uniformly dispersed silver-coated copper slurry is obtained.

[0036] Example 4 A silver-clad copper paste based on heterojunction, calculated by mass grouping, includes: #1 silver-coated copper powder 42.58%, #2 silver-coated copper powder 20.70%, submicron silver powder 18.94%, microcrystalline ultrafine silver powder 9.75%, epoxy resin 2.12%, epoxy curing agent 0.08%, phenoxy carrier 0.32%, DCAC solvent 5.49%.

[0037] According to the above preparation process, a uniformly dispersed silver-coated copper slurry is obtained.

[0038] Example 5 A silver-clad copper paste based on heterojunction, calculated by mass grouping, includes: #1 silver-coated copper powder 59.83%, #2 silver-coated copper powder 3.77%, submicron silver powder 23.86%, microcrystalline ultrafine silver powder 5.02%, epoxy resin 2.17%, epoxy curing agent 0.05%, phenoxy carrier 0.44%, DCAC solvent 4.87%.

[0039] According to the above preparation process, a uniformly dispersed silver-coated copper slurry is obtained.

[0040] Comparative Example 1 A silver-clad copper paste, calculated by mass grouping, includes: #1 silver-coated copper powder 50.65%, submicron silver powder 24.55%, microcrystalline ultrafine silver powder 5.15%, micron silver powder 11.73%, epoxy resin 1.39%, epoxy curing agent 1.20%, phenoxy carrier 0.39%, DCAC solvent 4.94%.

[0041] The main difference between the comparative example and the embodiment is that micron silver powder is used instead of high silver silver-containing copper powder, and the silver content of the slurry is controlled at about 45%. The micron silver powder is in the form of flakes. 50 The particle size of the silver-coated copper paste is 3.56 μm. According to the above preparation process, a uniformly dispersed silver-coated copper paste is obtained.

[0042] Comparative Example 2 A silver-clad copper paste, calculated by mass grouping, includes: #1 silver-coated copper powder 42.94%, #2 silver-coated copper powder 20.32%, submicron silver powder 19.10%, microcrystalline ultrafine silver powder 9.97%, epoxy resin 2.40%, epoxy curing agent 0.20%, DCAC solvent 5.07%.

[0043] The main difference between this comparative example and the example is that no phenoxy carrier is added, and a uniformly dispersed silver-coated copper slurry is obtained according to the above preparation process.

[0044] Comparative Example 3 A silver-clad copper paste, calculated by mass grouping, includes: #1 silver-coated copper powder 46.51%, #2 silver-coated copper powder 11.40%, submicron silver powder 18.82%, micron silver powder 15.78%, epoxy resin 1.31%, epoxy curing agent 0.10%, phenoxy carrier 0.52%, DCAC solvent 5.56%.

[0045] The main difference between this comparative example and the embodiment is that micron silver powder is used instead of microcrystalline ultrafine silver powder, and a uniformly dispersed silver-coated copper paste is obtained according to the above preparation process.

[0046] Comparative Example 4 A silver-clad copper paste, calculated by mass grouping, includes: #1 silver-coated copper powder 46.20%, #2 silver-coated copper powder 13.70%, submicron silver powder 20.18%, microcrystalline ultrafine silver powder 13.12%, epoxy resin 1.28%, epoxy curing agent 0.1%, phenoxy carrier 1.25%, DCAC solvent 4.17%.

[0047] The main difference between this comparative example and the embodiment is that the ratio of the epoxy resin to the phenoxy resin used exceeds 1:0.15 and reaches 1:0.23. According to the above preparation process, a uniformly dispersed silver-coated copper paste is obtained.

[0048] The proportions of the components in the embodiments and comparative examples are shown in Table 2: The above embodiments and comparative examples were tested for performance: Electron microscopy and element distribution: Zeiss scanning electron microscope Sigma 300 equipped with Oxford X-act energy dispersive spectrometer was used for testing.

[0049] Particle size distribution: The BT-2003 laser particle size analyzer produced by Dandong Better Instrument Co., Ltd. was used to test according to the national standard GB / T 19077-2016 to obtain the D 10 , D 50 , D 90 Equal particle size data.

[0050] Tap density: tested using BT-1000 powder comprehensive characteristic analyzer produced by Dandong Better Instrument Co., Ltd. in accordance with national standard GB / T 21354-2008.

[0051] Specific surface area: The surface area was tested using the Monosorb surface area analyzer produced by Quantachrome Instruments in accordance with GB / T 19587-2017 / ISO 9277:2010.

[0052] Resistivity: The silver-coated copper paste is screen-printed on a glass substrate. Figure 4 The circuit shown has a total length of 1000mm and a width of 0.3mm. The printed circuit is baked at 200℃ for 30 minutes, and then the circuit resistance R is tested using a multimeter. The film thickness of the circuit after baking can be measured by a Mitutoyo thickness gauge to obtain the film thickness h. The volume resistivity ρ of the silver-clad copper paste can be calculated by the following formula: ρ = R*0.3*h / 1000 Adhesion: Refer to the national standard GB / T 18-2017 and use the grid knife tool test kit to cut into 10x10 small grids of 1mm x1mm, and test with No. 600 tape produced by 3M.

[0053] The test results are shown in Table 3: From the test results, it can be seen that the silver content corresponding to Examples 1-5 decreases successively, namely 49.25%, 42.57%, 40.02%, 37.09% and 35.61%, respectively. The silver content is all below 50%, and the volume resistivity of Examples 1-5 is 6.15, 7.64, 7.03, 7.78 and 7.41 μΩ·cm, respectively. Comparative Example 1 does not add high-silver silver-containing copper powder, and only regulates the overall silver content by pure silver powder, which is a common method in the prior art. From the test results, its resistivity is much greater than that of each embodiment. In Comparative Example 2, no phenoxy carrier is added. Compared with Example 4, at a similar silver content, the experiment found that not only the group of electrodes is more brittle as a whole, but also the conductivity has significantly declined. In Comparative Example 3, no microcrystalline ultrafine silver powder is added. Compared with Example 3, the resistivity is significantly improved at a similar silver content, indicating that the presence of microcrystalline ultrafine silver powder with a special structure can further improve the electrical properties of the silver-coated copper paste of the present invention. In Comparative Example 4, too much phenoxy resin was added. Experiments have shown that too much thermoplastic resin leads to poor contact between the silver-coated copper powders, reduced conductivity, and reduced mechanical properties of the overall electrode, making it difficult to meet the requirements of HJT battery cells.

[0054] The embodiments described above are merely descriptions of preferred implementations of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope of the present invention.

Claims

1. A silver-coated copper paste based on heterojunction, comprising the following components: Silver-coated copper powder, submicron silver powder, binder, curing agent and solvent; Features: The silver-coated copper powder is a combination of low-silver-containing silver-coated copper powder and high-silver-containing silver-coated copper powder; The silver content of the low-silver silver-coated copper powder is less than 15%, and the silver content of the high-silver silver-coated copper powder is greater than 15%; The low-silver silver-containing copper powder accounts for 5-70% of the total mass, and the high-silver silver-containing copper powder accounts for 1-50% of the total mass; The binder is a combination of a thermosetting resin and a thermoplastic resin.

2. The silver-coated copper paste based on heterojunction according to claim 1, characterized in that: Also included is microcrystalline ultrafine silver powder.

3. The silver-coated copper paste based on heterojunction according to claim 1, characterized in that: The thermosetting resin is epoxy resin, and the thermoplastic resin is phenoxy resin.

4. The silver-coated copper paste based on heterojunction according to claim 3, characterized in that: The epoxy resin is a combination of one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin and glycidyl ester epoxy resin.

5. The silver-coated copper paste based on heterojunction according to claim 1, characterized in that: The low-silver silver-containing copper-coated powder is a mixed powder of spherical and flake shapes, with a particle size of D 50 1.0-5.0μm.

6. The silver-coated copper paste based on heterojunction according to claim 1, characterized in that: The high-silver silver-containing copper-coated powder is a spherical powder with a particle size D 50 2.0-6.0μm.

7. The silver-coated copper paste based on heterojunction according to claim 1, characterized in that: The curing agent includes one or more of a latent epoxy curing agent and an isocyanate latent curing agent.

8. The silver-coated copper paste based on heterojunction according to claim 7, characterized in that: The isocyanate latent curing agent is a combination of one or more of toluene diisocyanate, diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, hexylene diisocyanate, xylylene diisocyanate and isophorone diisocyanate.

9. The silver-coated copper paste based on heterojunction according to claim 1, characterized in that: The solvent is a combination of one or more of diethylene glycol ethyl ether acetate, butyl carbitol acetate, dibasic acid ester, terpineol, ethylene glycol butyl ether acetate, and butyl carbitol.

10. Use of the silver-coated copper paste based on heterojunction according to any one of claims 1 to 9 in preparing a gate electrode.

Citation Information

Patent Citations

  • Silver paste for heterojunction battery, and preparation method and application thereof

    CN113284644A

  • Low-silver heterojunction-containing silver-coated copper slurry and preparation method thereof

    CN117352207A